The Effect of Anti-Stripping Agent Addition on the Performance of Asphalt Concrete-Wearing Course (AC-WC) Mixture with Madura Local Aggregate - Muhammad Nur; Ibnu Sholichin; Achmad Alfiansyah (Indonesian Journal Publisher, 2025)
This study investigates the use of the Morlife 300 anti-stripping agent to improve the performance of Asphalt Concrete–Wearing Course (AC-WC) mixtures incorporating local aggregates from Madura Island, Indonesia. The objective of this research is to determine the Marshall characteristics of the mixture and to identify both the optimum asphalt content and the optimum anti-stripping dosage based on the 2018 Bina Marga Specifications (Revision 2). Laboratory testing was conducted using asphalt contents of 5%, 6%, and 7%, resulting in an optimum asphalt content of 5.2%, while additive variations of 0%, 0.1%, 0.3%, and 0.5% were used for performance evaluation. The results show that the incorporation of Morlife 300 enhances mixture performance, as indicated by decreasing Air Voids and Voids in Mineral Aggregate and increasing Voids Filled with Asphalt, along with improved stability and Marshall Quotient values. Compared to the mixture without additive, the use of 0.3% Morlife 300 increases stability by 30.57% and the Marshall Quotient by 29.38%, marking this dosage as the optimum level among all variations tested. Overall, the use of the Morlife 300 anti-stripping agent is proven to improve the volumetric and mechanical performance of AC-WC mixtures.